Autophagy-Inflammation Interplay During Infection: Balancing Pathogen Clearance and Host Inflammation - Pang, Yuqian; Wu, Lanxi; Tang, Cheng; Wang, Hongna; Wei, Yongjie (Frontiers in Pharmacology, 2022)
Inflammation is an essential immune response of the host against infections but is often over-activated, leading to a variety of disorders. Autophagy, a conserved degradation pathway, also protects cells by capturing pathogens that enter the cell and transporting them to the lysosome for clearance. Dysfunctional autophagy is often associated with uncontrolled inflammatory responses during infection. In recent years, more and more research has focused on the crosstalk between autophagy and inflammation. In this paper, we review the latest research advances in this field, hoping to gain insight into the mechanisms by which the body balances autophagy and inflammation in infections and how this mechanism can be used to fight infections better.